(3CNOhO GdHYK (B:s (3QhGjI (B/s - (3GdHNGQj, GdMSfs ((3dfOf (B:s (3OGQ QhGjI,s, 2020)
(3QhGjI (B"(3CNOhO GdHYK(B" (3JeKd HOGjI WaQI aj hUajI COH GdQhGjI aj JfXjQGJ GdUMhI GdESdGejI, QhGjI JLSO GdUQGY Hjf GdMb hGdHGWd, hGdNjQ hGdTQ aj CHgQ UhQI, hJMV Ydi bje GdaVjdI HCSdhH bTjH hQTjb(B.s
Keywords: (3GdbUU GdYQHjIs -- (3bUU OjfjIs -- (3QhGjIs -- (3eUQs -- (3bQf (B21s